Urban overspill and its upshot to the Bafoussam Emergent Metropolis in Cameroon - Tende, Renz Tichafogwe; Kengmoe, Emmanuel Tchouongsi (Advances in Social Sciences Research Journal, 2020)
Unbridled urban sprawl in Sub-Saharan African cities reflects an infirmity that warrants both vaccination and treatment to curb urban disorder and its costs. This article divulges that rapid population growth, spatial expansion and economic activities are responsible for the urban overspill and its upshot in Bafoussam. Unplanned settlement from the rapid growing population has led to the development of slumps and reduction of arable land. A multi-spectral Landsat satellite imagery of 1988, 2001 and 2016 was used to determine the spatial expansion of the town over a period of 30 years. Field observation and interview sessions were done to have information on the proliferation of economic activities to the expansion of the town. An in-depth secondary data collection was done to gather information on the rate of population growth of Bafoussam. The data was processed to generate maps through the ArcGIS 10.4 and Adobe Illustrator CS soft wares and tables through SPSS 17 for results and analyses. Results from findings propound a significant increase in the built-up area of Bafoussam of 19.34% in 1988, 50.30% in 2001 and 79.41% in 2016. This increase was accompanied by a drop in the vegetation of 78.64% in 1988, 48.50% in 2001 and 20.07% in 2016. The built-up increase was provoked by a persistent rise in the population of the city from 62, 239 inhabitants in 1976 to 112,681 in 1987 and 282,800 in 2010. Industrial and commercial activities developed in the course of the twin increase and unfortunately with no control triggered urban disorder. This article advocates for a mandatory implementation of the urban norms in Cameroon to liberate Bafoussam from the drowning overspill syndrome plaguing Sub-Saharan cities.